The Development of the Turkish Minority’s Social Challenges in Denmark from 1970 to 2021, for the Purpose of Integration - Merve Sahin (Turkish Journal of Diaspora Studies, 2022)
Beginning in the 1960’s, Denmark recruited Turkish guest workers. Today, the Turkish minority is Denmark’s largest minority group from non-western countries. This article examines the social challenges of the Turkish minority in Denmark from 1970 to 2021, and their integration during this period. This study uses several methods to obtain insight into the integration process of Turkish immigrants over three generations in Denmark and the challenges they faced and continue to face. In addition to the source criticism and a comprehensive literature review, this study uses qualitative and quantitative methods to understand Turkish immigrants’ immigration processes. Qualitative and quantitative analysis in the field of Danish historical research, specifically the area concerning the Turkish minority are not adequately covered by the existing literature. This study finds that all three generations of the Turkish minority in Denmark experienced social challenges in several areas that are related to each other, and these social challenges have an effect on their integration status. Some social challenges have decreased over generations but specifically discrimination and racism have not.